RoombaNet - Testbed for Mobile Networks - Hail, Mohmaed; Pinkowski, Jan; Teubler, Torsten; Danckwardt, Maick; Pfisterer, Dennis; Hellbrück, Horst (Electronic Communications of the EASST, 2011)
The design and deployment of wireless networks needs careful planning including various tools for analysis, simulation and evaluation. Therefore, development of software to support deployment of wireless networks has been subject of intensive research for several years. In particular the evaluation of the influence of mobility remains a challenging task. For deployment of mobile communication networks operators perform simulations and measurements during the planning process with large efforts. In the past the research community based their decisions on development of new protocols on simulations exclusively. While network simulators provide fast investigation of huge and also mobile networks they rely on theoretical models which are often considered as inaccurate and too optimistic. Therefore, more and more real wireless network environments called testbeds are established worldwide most of them with static nodes. Testbeds dedicated towards mobile networks remain a challenge as the effort to build such a network increases with mobility. The work here presents an approach for a fully automated real-world mobile network testbed where nodes are piggybacked on mobile robots. The platform with up to 30 mobile nodes and additional 30 static nodes can emulate various scenarios especially suited for pedestrian scenarios or for slow car movements. In this paper we introduce this testbed which is integrated into the larger Real-World GLab Internet testbed facility. We provide first details of the hardware and software components and provide first evaluations as well as present application examples.